(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
This article financial to the report given definitions Uzbekistan " Accounting " of the Republic account "about" Law , accounting account national standards (BHMS), financial of the report international standards (IFRS) and advanced foreign textbooks point of view from the point of view in detail analysis does . Financial report of the enterprise financial status , activity results and money currents reflection provider transparent information source as is described . In the article national and international standards between comparison , their harmony process ( this including in Uzbekistan starting in 2021 large enterprises for To the IFRS transition and continue arriving reforms ) are highlighted . The analysis is as follows shows that the IFRS adaptation financial transparency increasing , foreign investments attraction to do service As a result , businesses and state organs for IFRS current to grow according to recommendations given.